A Integrating Arabic Language Instruction into Qur’anic Literacy Training: A Program for Non-Formal Learners - Retno Intan Kuswari; Muhammad Fathur Ro'uf; Ana Durrotul Hikmah; A’an Yusuf Khunaifi; Filzatun Nafsi (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Purpose: This research aims to address the low proficiency in Qur’anic literacy among equivalence education students at PKBM Alfasalam by implementing and evaluating an applicative and contextual Arabic language learning method. Method: This study employs a qualitative descriptive method. Primary data were collected through structured observations and in-depth interviews with students, while secondary data were obtained from a review of relevant journals and program documents. Data analysis followed a thematic approach to identify key patterns and outcomes. Findings: The implementation of practice-based training, utilizing fun learning and contextual teaching and learning (CTL) approaches over a two-month period, resulted in measurable improvements. Pre- and post-activity assessments showed a significant increase in students' ability to read the Qur’an with proper tajwid. Observational data confirmed enhanced engagement and accuracy in recitation. Conclusion: The activity concluded with positive feedback from students, tutors, and guardians. The results indicate that the applicative-contextual method effectively improves Qur’anic literacy skills. It is recommended that such programs continue and expand to reinforce learning outcomes, with the long-term goal of enabling students to not only recite correctly but also comprehend and apply the teachings in daily life.